Effects of n-3 and n-6 feeding sources on the quality and lipid oxidation of meat from feedlot-finished Bos indices steers - Costa, Fabiane S.; Cabral, Anderson R.; Silva, Saulo L.; Silva, Marilia A.; Henrique, Wignez; Mazalli, Monica R.; Baldi, Fernando S. [UNESP]; Mueller, Lenise F.; Ferrinho, Adrielle M.; Corte, Rosana R. P. S.; Pereira, Angelica S. C. (Elsevier B.V., 2020)
This study was conducted to evaluate the fatty acid profile, sensory properties and lipid oxidation of meat on retail display (RD) from Nellore steers (n = 96) fed diets containing soybean (SOY), sunflower (SUN), or linseed (UN) oil or a control diet (CON). After slaughtering, samples of the Longissimus muscle were collected for sensory properties (1 day), fatty acid composition (1 day) and oxidation stability (3 days under RDC) evaluations. No differences in total lipids, cholesterol, TBARS, and total SFAs, MUFAs, PUFAs, and PUFA/SFA were observed. However, meat from animals fed vegetable oil had more CLA than that of the CON samples. The flavour, juiciness and overall acceptability were affected by the treatments (P < 0.05), but no consistent effect of a specific oil source was observed. Meat colour was not affected by diets or days under RD, and 7-ketocholesterol was not detected in any sample. The oil sources used in this work were not effective in consistently changing meat properties.
Keywords: Sensory analysis; Linseed; Sunflower; Soybean; Cholesterol oxide; Alfa-linolenic acid